Hydraulic forces acting on full cross section fuel assemblies with 17×17 fuel rods. (December 2020) - Bieder, Ulrich; Genrault, Clarisse; Ledac, Pierre
Abstract: The pressure and velocity distribution within and between full cross-section fuel assemblies with generic but realistic mixing grids are analyzed by CFD using high performance computing (HPC). The reference fuel assembly consists of a bundle of 17 × 17 rods, including fuel rods, control rod guide tubes and a mixing grid with split type mixing vanes. The axial length of the analyzed domain spans approximately the interval between two successive mixing grids. Only hydraulic effects of the mixing grids on the behavior of the flow are analyzed, power input and heat transfer are not considered. The presented results are based on a well-validated calculation procedure. The intra-assembly exchanges and pressure fields were analyzed by modelling one single assembly, whereas the inter-assembly exchanges and pressure fields were analyzed by modelling a group of three horizontally aligned fuel assemblies, each build of 17 × 17 rods and a mixing grid. In the multi-assembly test cases, the water gaps that separate the central assembly from the neighboring fuel assembles vary between 2 mm and 10 mmm. In one additional test case, the rods of the central fuel assembly were slightly inclined in order to treat deformed assemblies. For a fuel assembly that is surrounded by water gaps of 2 mm, the total force (pressure and shear force) acting in flow direction upon one mixing grid is about 230 N. The total force working on the grid in cross flow direction is small. The prediction of this horizontal force can be falsified by inappropriate boundary conditions as symmetry. The total force acting upon the rods is about 160 N in flow direction and small in crossflow direction. Variations in the width of two oppositely located water gaps significantly influence the pressure force that is acting on the mixing grid in horizontal direction. Depending on the difference in the width of the water gaps, pressure forces of 39 N and 24 N were calculated for gap couples of 2 mm and 5 mm, and of 3 mm and 7 mm, respectively. This horizontally acting pressure force ( Venturi force) tries to push the assembly in the direction to homogenize the water gap widths (self-stabilizing effect). The inclination of the rods of the central assembly does not lead to significant forces in cross flow direction. In order to assure this result, a calculation with very fine meshing (1000 million tetrahedrons) was performed. Graphical abstract: Hydraulic forces on fuel assemblies with different sizes of water gaps are calculated by using the CFD code TrioCFD. Meshes with up to 1 billion cells were used. Group of 3 fuel assemblies; arrangement of the assemblies and visualization of the inter-assembly flow exchanges by a tracer. Forces in flow direction and in crossflow direction were quantified. The influence of boundary conditions on the prediction of forces is discussed. The horizontally acting pressure force ( Venturi force) affects the fuel assemblies in the reactor core in a way that the force tries to adjust automatically the width of water gaps to similar values (self-stabilizing effect). Image 1 Highlights: Hydraulic forces acting on fuel assemblies with 17 × 17 fuel rods were analyzed. The influence of the width of water gaps on pressure and shear forces is addressed. Hydraulic forces on inclined rods were quantified with a fine mesh of 1 billion tetrahedrons. The total hydraulic force acting on a mixing grid is flow direction is about 230 N. The pressure force in cross flow direction is about 39 N for 3 mm difference in water gap width.